Modeling, Simulation and Control of a Redundant Scara-Type Manipulator Robot - Urrea-Onate, E; Kern-Molina, J (2012)
In this paper, the modeling of a redundant SCARA-type manipulator robot with five degrees of freedom is presented. We propose three controllers - hyperbolic sine-cosine, sliding mode, and calculated torque -which are applied to the discussed model. A simulation environment is developed using MatLab/Simulink programming tools. This simulation environment is employed to perform several tests (including actuators- dynamics) on the model of the redundant manipulator, with each different controller, under path tracking requirements. Results were obtained from comparative curves and rms index for joints and Cartesian errors. © 2012 Urrea and Kern.
Keywords: Redundant manipulators; dynamic model; controllers; simulation